Long-term incidence of cardiac device complications with intrathoracic versus extrathoracic venous access: results from the PLACE (Planning Lead Access for Cardiac Electrostimulation) study. (19th May 2022) - Ghiglieno, C; Dell' Era, G; Palmisano, P; Floris, R; Pimpini, L; Coluccia, G; Delogu, G; Colombo, C; Marconetto, C; De Zan, G; D'amico, A; Mazzoleni, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Optimal venous access is crucial in successful cardiac device implantation. Most commonly used accesses are subclavian or axillary vein puncture and cephalic vein cutdown. The extrathoracic access has the advantage of reducing the risk of pneumothorax and lead disfunction; thus, this approach is recommended as the first choice approach. Purpose: The aim of our retrospective registry was to evaluate the incidence of long-term device complications (pneumothorax, lead rupture or displacement, hematoma, infection or bleeding) with different venous approaches in four high-volume centers in Italy. Methods: We collected data from implantation and device complications during follow up using available electronic records from each center. Results: We included 4443 patients, mean age 73±11 years. Median follow up was 118 months (IC range 59-198 months). The incidence of any complication was 7.7 %, without difference between intrathoracic and extrathoracic access (7.8% vs 7.7% respectively, p=0.70). However, lead rupture was more frequent in the intrathoracic group (5.3% vs 1.4%, p=0.04). Conclusion: In experienced, high-volume centers, the use of intrathoracic vein puncture in the case of unsuitable extrathoracic access may represent a safe alternative of venous access in patients undergoing cardiac device implantation, although associated with a higher occurrence of lead rupture.